The effect of spray-dried plasma source on starter pig performance - Smith, J.W. II; Richert, B.T.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 416 pigs (initially 9.36 Ib and 15 d of age) was used in a 28-d growth assay to evaluate the effects of spray-dried plasma source on starter pig performance. Pigs were blockedby weight and allotted to one of four dietary treatments in a randomized complete block design. Three spray-dried plasma sources were tested: bovine, porcine, and plasma collected from only sows. Plasma sources and lactose replaced skim milk in the control diet to form the experimental diets. Experimental diets were fed during Phase I (d 0 to 14 postweaning), and all pigs were fed a common Phase II (d 14 to 28 postweaning) diet. Phase I diets were formulated to 1.5% lysine and .42 % methionine. Phase II diets were formulated to 1.25% lysine and .36% methionine. Phase I diets were fed in a pellet form and Phase II in a meal form, and all diets were formulated to .9% Ca and .8% P. During Phase I, pigs fed diets containing porcine and sow plasma grew faster than the pigs fed the control and bovine plasma diets. Pigs fed either swine plasma source were more efficient than pigs fed the control diet. During Phase II, when pigs were fed a common diet, pigs that were fed diets containing sow and bovine plasma diets in Phase I had higher feed intakes than pigs that were fed the control diet. Overall (d 0 to 28), pigs fed the porcine plasma diet grew faster and pigs fed the sow plasma diet grew more efficiently than pigs fed the control diet. In conclusion, plasma source affects starter pig performance. Based on our results, plasma of porcine origin promoted greater ADG d 0 to 14 postweaning than bovine plasma.
Keywords: Swine; Starter performance; Plasma protein; Sources